Crystallization in Couette-Taylor Crystallizer: Effect of Taylor Vortices Flow on the Nucleation and Reconstruction of L-Glutamic Acid in Cooling Crystallization - Trinh, Huyen Thi Thanh; Nguyen, Tuan Anh; Phan, Thao Thanh; Khuu, Quang Chau; Le, Nhan Thi Hong; Dang, Giang Truong; Nguyen, Tuyet Dinh (Vietnam Journal of Science and Technology, 2016)
The effect of Taylor vortices flow of Couette-Taylor (CT) crystallizer on the nucleation and reconstruction of L-glutamic acid was firstly investigated in cooling crystallization. Generally, L-glutamic acid has two kinds of polymorphic crystal including metastable α-form and stable β-form, where the α-form is initially crystallized and then slowly transformed into the β-form, which is called the phase transformation. The present study explored that there was a significant difference between CT and the conventional ST crystallizer as regards the nucleation and reconstruction of L-glutamic acid. Here, the phase transformation determined by the nucleation and reconstruction was 40h in ST crystallizer, yet it was only 20h as using the CT crystallizer, implying that the nucleation and reconstruction of L-glutamic acid was facilitated 2.0 times as using the Taylor vortices flow. The advantage of Taylor vortices flow in CT crystallizer over the random fluid motion in ST crystallizer with regard to the nucleation and reconstruction was explained in terms of the high energy dissipation of Taylor vortices flow.